GE_GERICHTE P/2209/2019 vom 12. Februar 2019 - GE Cour de justice (2019)
LÉSION CORPORELLE GRAVE ; VIOLATION DE DOMICILE ; ACCÈS INDU À UN SYSTÈME INFORMATIQUE | CPP.310; CP.122; CP.144; CP.186; CP.143bis